THE CONCEPTUAL FRAMEWORK FOR FINANCIAL REPORTING AND ITS CONTRIBUTION TO THE IMPROVEMENT OF FINANCIAL REPORTING QUALITY - Lina Khalid jaafer Ibrahim (Scholar Express Journals, 2025)
The research aims to clarify the adoption of the application of the conceptual framework for financial reporting and its role in improving the level of quality of financial reports on the one hand, and to push banks towards adopting the conceptual framework for financial reporting in preparing and presenting reports and financial statements on the other hand. The student relied on the questionnaire form as a study tool, and the study was applied to a sample. Of the private commercial banks listed on the Iraq Stock Exchange, their number reached (17). (158) questionnaires were distributed to the sample members, of which (144) questionnaires were returned, amounting to (94) of the questionnaires recovered and valid for analysis. One of the most important findings of the research is the existence of a positive, statistically significant relationship between the application of the conceptual framework for financial reporting and its impact on the quality of financial reports, and that the financial work environment becomes supportive and enhancing the adoption of the application of the conceptual framework for reporting when that framework provides the requirements of suitability and reliability for the informational content of financial reports according to the needs of users. The application of the conceptual framework for financial reporting positively affects the suitability and reliability characteristic and increases the accuracy of the information contained in banks’ financial reports.
Keywords: Financial reporting; report quality; conceptual framework